A rapid and sensitive lateral flow immunoassay (LFIA) for the detection of gluten in foods. (1st September 2021) - Hnasko, Robert M.; Jackson, Eric S.; Lin, Alice V.; Haff, Ronald P.; McGarvey, Jeffery A.
Highlights: Monoclonal antibodies for sensitive and selective gluten detection. Rapid gluten detection (<5 min) by lateral flow immunoassay. A single-use biosensor for easy gluten testing of foods. Abstract: The gluten protein found in a variety of cereal grains is a food allergen that can elicit a spectrum of immuno-inflammatory responses in people. Consumer awareness has prompted changes in food labeling requirements, expanded gluten-free food product availability and increased demand for effective gluten testing methodologies. To meet the challenges associated with gluten testing from diverse and complex foods we developed a lateral flow immunoassay (LFIA) using a pair of novel gliadin monoclonal antibodies (MAbs). Using a visual gold reporter, we show sensitive gluten detection (150 ng/mL) from complex food substrates using a fast (<5 min) and easy testing methodology. In this report we characterize the binding properties of a cohort of newly generated gliadin monoclonal antibodies suitable for gluten detection using multiple assay formats and introduce a novel plug- n -play test strip platform with integrated test components in a single-use format.